Directions of effective development of cable industry companies - Семенова, Валентина Григорівна (Technology audit and production reserves, 2015)
Economic crisis in Ukraine, increased competition and the challenge of integrating into the world economy are need make every effort from Ukrainian producers to overcome all obstacles. Internal and external economic and social threats can be overcome only company focused on the development and ongoing compliance with the requirements. For companies of cable industry of electrical field are certainly inherent qualities necessary for successful development even in difficult economic conditions. International experience shows the growth in demand for products the cable industry, which is now used in almost all sectors of the economy and human activity. However, there are many problems and market risks for cable production market related to the lack of proper government regulation of business areas, increased competition in the global market of cable products, aggravation of the crisis in Ukraine, the lack of domestic raw materials, limitation of investment for innovation funding. The features of the cable industry as one of the promising high technology industries are investigated. General trends in the market of cable products in the modern business environment are revealed. Main problems and risks of the operation of cable industry companies in Ukraine are determined. The main directions of effective development of cable industry companies are developed. The results of the research can be implemented in practice of cable companies to determine promising activities and strategies for future development.